Stymie patterns: The case of French-language learning in Indonesian universities - Merry Andriani; Wening Udasmoro; Roberta Salsano; Tri Indri Hardini (Universitas Pendidikan Indonesia, 2022)
Learning languages is inevitably related to one’s learning culture and patterns. Despite the existence of different language learning strategies in Indonesia, students’ achievements in general show unsatisfying facts. Several learning patterns have the potential to stymie foreign-language learning at particular educational levels. Those learning patterns are the accumulation of a long traditions and practices in teaching and learning of foreign languages. This study examined the practices of teaching and learning French as a foreign language at two universities in Indonesia. These institutions were selected based on their approaches to teaching and learning the language; one employs a pedagogic approach, while the other applies a generalist approach. Data were collected through in-depth interviews with nine students and six lecturers, as well as observation of four classes between March 2016 and October 2017. The data were subsequently selected and analyzed with a didactic of foreign language methodology. The methodology was based on a post structural paradigm with an emphasis on intertextuality and interdiscoursivity. This method implied the approach to discourse analyses referred to the French perspective. Results from the analysis showed that the universities tended to teach French with a repetitive and uniform approach. The most prominent didactic technique was rote memorization through mnemonics, which permeated almost all aspects of learning the foreign language. The failure to combine this technique with other learning strategies stymied students' efforts to learn the language.